The impact of attentional, linguistic, and visual features during object naming - Clarke, Alasdair D.; Coco, Moreno I.; Keller, Frank (Frontiers in Psychology, 2013)
Object detection and identification are fundamental to human vision, and there is mounting evidence that objects guide the allocation of visual attention. However, the role of objects in tasks involving multiple modalities is less clear. To address this question, we investigate object naming, a task in which participants have to verbally identify objects they see in photorealistic scenes. We report an eye-tracking study that investigates which features (attentional, visual, and linguistic) influence object naming. We find that the amount of visual attention directed toward an object, its position and saliency, along with linguistic factors such as word frequency, animacy, and semantic proximity, significantly influence whether the object will be named or not. We then ask how features from different modalities are combined during naming, and find significant interactions between saliency and position, saliency and linguistic features, and attention and position. We conclude that when the cognitive system performs tasks such as object naming, it uses input from one modality to constraint or enhance the processing of other modalities, rather than processing each input modality independently.